To the arguments about Leonov’s novel "The thief" - Lysov, A. (Literatūra, 1974)
Arguments that have arisen lately about "The Thief" by L. Leonov were caused by the publication of its second version. Positively estimating this new version of the novel critics are apt to consider that the first version was the result of the author’s mistakes: the absence of social determination of the characters is underlined. The article shows that the first version of "The Thief" is the result of Leonov’s meditation about the formation of new man. This problem joins the novel with actual questions of the epoch. In the first wording the appearance of new man is determined by the hero’s acceptance of old humanistic conceptions which affirm value and individuality of man. In the second wording of "The Thief" the appearance of new man is possible only after his adoption of socialist moral which is, in its turn, the continuation of the old humanistic ideas. However, in both versions of "The Thief" the hero’s new spiritual level is due to the laws of logical and historical causality.